2011
DOI: 10.1124/jpet.110.174268
|View full text |Cite
|
Sign up to set email alerts
|

S-Adenosylmethionine Decreases Lipopolysaccharide-Induced Phosphodiesterase 4B2 and Attenuates Tumor Necrosis Factor Expression via cAMP/Protein Kinase A Pathway

Abstract: S-Adenosylmethionine (SAM) treatment has anti-inflammatory, cytoprotective effects against endotoxin-induced organ injury. An important component of the anti-inflammatory action of SAM involves down-regulation of the lipopolysaccharide (LPS)-induced transcriptional induction of tumor necrosis factor-␣ (TNF) expression by monocytes/macrophages. We examined the effect of SAM on expression and activity of LPS-induced up-regulation of phosphodiesterase 4 (PDE4), which regulates cellular cAMP levels and TNF express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 54 publications
2
54
0
Order By: Relevance
“…Soluble TNF-␣ release from cells requires the posttranslational cleavage of a pro-TNF-␣ form by the TNF-␣-converting enzyme (TACE; ADAM-17) (21). Evidence exists that cAMP-PKA activation blocks TNF-␣ expression (9) and that cAMP-elevating agents inhibit TACE activity in alveolar epithelial cells (25). Moreover, swine CAFO dust-stimulated TNF-␣ gene expression was inhibited by cAMP in alveolar epithelial cells (7).…”
mentioning
confidence: 99%
“…Soluble TNF-␣ release from cells requires the posttranslational cleavage of a pro-TNF-␣ form by the TNF-␣-converting enzyme (TACE; ADAM-17) (21). Evidence exists that cAMP-PKA activation blocks TNF-␣ expression (9) and that cAMP-elevating agents inhibit TACE activity in alveolar epithelial cells (25). Moreover, swine CAFO dust-stimulated TNF-␣ gene expression was inhibited by cAMP in alveolar epithelial cells (7).…”
mentioning
confidence: 99%
“…Work done by our group demonstrated that histone lysine 9 trimethylation (H3K9me3) in the Pde4b2 intronic promoter region plays a major role in regulating endotoxin responsive PDE4B2 mRNA expression in macrophages [137]. Specifically, a rapid and significant decline in the PDE4B2…”
Section: Future Directionsmentioning
confidence: 99%
“…These data strongly support the notion that alcohol predominantly affects PDE4B expression that affects brain cAMP metabolism. Although, LPS through TLR activation is a strong driver of PDE4B expression in peripheral monocytes/macrophages, it is well-documented that very little peripheral LPS gains access to the brain due to the poor passage through the blood brain barrier [135][136][137]221]. Hence, the alcohol-induced systemic endotoxemia likely plays an indirect role in inducing brain PDE4B expression and inflammation via the triggering of systemic cytokines such as TNF.…”
Section: The Effect Of Pde4 Inhibition On Glial Activation and Inflammentioning
confidence: 99%
See 2 more Smart Citations